1995
DOI: 10.1042/cs0880141
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Platelet-Derived Growth Factor-Induced Expression of Vascular Permeability Factor Mrna by Human Vascular Smooth Muscle Cells In Vitro

Abstract: 1. Endothelial dysfunction and vascular smooth muscle cell (VSMC) proliferation are key events in the pathogenesis of atherosclerosis. Vascular permeability factor (VPF), an endothelial-cell-specific multifunctional cytokine, was recently described, and has the potential to contribute to the development of endothelial dysfunction. The present study determines whether cultured human VSMCs express mRNA for VPF and whether VPF mRNA expression is influenced by human VSMC proliferation. 2. A 204 bp cDNA fragment, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…21 Both PDGF and bFGF are involved in tumor proliferation 22,23 and induce VEGF. 24,25 PDGF is a pericyte mitogen that plays an important role in the regulation of angiogenesis, 26 -28 and is also reported to be a permeabilizing agent. 29 SU6668 is an inhibitor of the tyrosine kinase receptors for the above-described 3 angiogenesis factors, and is characterized by its broad spectrum of action.…”
Section: Discussionmentioning
confidence: 99%
“…21 Both PDGF and bFGF are involved in tumor proliferation 22,23 and induce VEGF. 24,25 PDGF is a pericyte mitogen that plays an important role in the regulation of angiogenesis, 26 -28 and is also reported to be a permeabilizing agent. 29 SU6668 is an inhibitor of the tyrosine kinase receptors for the above-described 3 angiogenesis factors, and is characterized by its broad spectrum of action.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, phorbol esters stimulate mesangial VEGF production [139] and notably, inhibition of PKC blocks VEGF signalling [140]. Further, various growth factors and cytokines, including TGF-b [141,142], IGF-I [143], basic fibroblastic growth factor (bFGF) [144] and platelet derived growth factor (PDGF) [136,145] have been shown to stimulate VEGF production in various non-renal cell types. Finally, as mentioned above, both IGF-I [79] and VEGF [80] stimulate NF-kB concentrations in endothelial cells in vitro.…”
Section: In Vitro Evidence For Vegf Effects On Kidney Cellsmentioning
confidence: 99%
“…ecently there has been marked progress in the study of growth factors and of these, basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF) are known for their widespread distribution in vivo, [1][2][3] as well as their strong angiogenetic effect in ischemic animal models. [4][5][6][7] Recent experimental studies have demonstrated that exogenously administered bFGF and VEGF augmented collateral vessel development in animal models of hindlimb ischemia, 4,5 and they also showed an effect in reducing the infarcted myocardium in canine coronary occlusion.…”
mentioning
confidence: 99%